Illuminating Siderophore Transporter Functionality with Thiopeptide Antibiotics - Stephen K. Dolan (mBio, 2023)
ABSTRACT The Gram-negative opportunistic pathogen Pseudomonas aeruginosa is a leading cause of infections and mortality in immunocompromised patients. This organism can overcome iron deprivation during infection via the synthesis of two iron-chelating siderophores, pyoverdine and pyochelin, which scavenge iron from host proteins. P. aeruginosa can also uptake xenosiderophores produced by other bacteria or fungi using dedicated transporter systems. The precise substrate specificity of these siderophore transporters remains to be determined. The thiopeptide antibiotic thiostrepton exploits the pyoverdine transporters FpvA and FpvB to cross the outer membrane and reach intracellular targets. Using a series of intricate biochemical experiments, a recent study by Chan and Burrows capitalized on the specificity of thiostrepton to uncover that FpvB transports the xenosiderophores ferrichrome and ferrioxamine B with higher affinity than pyoverdine. This surprising result highlights an alternative uptake pathway for these siderophores and has significant implications for our understanding of iron acquisition in this organism.